Pushed to the periphery: A review of the literature on the salient issues facing internationally educated teachers in the Canadian education system - Skelton, Lucas (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2026)
This article offers a review of the research on the issues facing internationally educated teachers (IETs) within the Canadian education system, including recertification and qualifications recognition, linguicism, and diversity, discrimination, and inclusion. Following an overview and analysis of these issues, the financial, academic, language, and acculturative support the IETs can access and the push to diversify the teaching force are explored as ways these educators endure the challenges. The final part of the article includes an overview of gaps in the literature including the lack of symmetry among provincial recertification processes throughout the country and a call for scholars to undertake studies to understand the IET experience and include these teachers in more significant numbers in the Canadian school system.